COMPARATIVE ANALYSIS OF ORAL SUBMUCOUS FIBROSIS AND LICHEN PLANUS: INSIGHTS FROM PATIENT SURVEYS - JAFFRI, SB; IRFAN, F; JAM, B; RAHMAT , B; PIRZADA, SA; SIBGHATULLAH, M (Biological and Clinical Sciences Research Journal, 2024)
Oral Submucous fibrosis (OSMF) and Lichen planus (LP) are chronic diseases of the oral mucosa that have different causes and manifestations. OSMF is primarily associated with betel quid chewers showing progressive fibrosis with functional derangement and a high propensity for malignant change. LP, on the other hand, is an immune-mediated disease that presents with a wide range of symptoms and contrarily, has a lower severity of complications associated with it. Although there is much written on both conditions’ knowledge of the relative clinical characteristics, psychological effects, and functional consequences of each is limited. Objective: The study offers a complete comparative evaluation of OSMF and LP concerning lesion typical presentation, symptoms’ severity, disorder’s psychological manifestations, and influence on oral function among the patients seen at Sindh Institute of Oral Health Sciences, Jinnah Sindh Medical University. Methods: A cross-sectional study was performed at Sindh Institute of Oral Health Sciences Karachi in July and August 2024. Altogether 100 patients diagnosed for OSMF and 100 patients diagnosed for LP were included in the study. Structured questionnaires and clinical examinations were used while collecting data. An evaluation was made of lesion characteristics, psychological responses, and functional consequences. Analysis of data was done by using the chi-square test for comparing two or more proportions, the t-test to compare two groups of independent variables, the U test for two independent samples which were not normally distributed, and logistic regression all from SPSS version 27.0. Results: OSMF patients were more likely to have lesions located on the cheeks (60%) and experience severe functional impairment which includes difficulty in chewing and swallowing. While LP patients presented more frequently with tongue lesions (45%) and less severe functional limitations. OSMF patients reported higher levels of psychological distress with 55% experiencing moderate to severe anxiety as compared to 30% in LP patients. Logistic regression identified lesion appearance, severity and impact on oral function as the main predictors of diagnosis (p < 0.05). Conclusion: This study enunciates a comparison in the Clinical manifestation, Psychiatric/ Psychological impact and Functional Profile of Oral Submucous Fibrosis with that of Lichen Planus. LP presents fewer complications, less apparent functional disability and a different distribution of the lesions than OSMF, which is associated with severe fibrosis and significantly poor oral function. These results provide a rationale for client-centred approaches to treatment that will enhance the physical and psychological well-being of the patients. Subsequent investigation is necessary to assess long-term manual and anti-psychotic efficacy.